Penerapan Model Pembelajaran Problem Based Learning (PBL) pada Keterampilan Menulis Teks Drama - Yuli Kiswanti (Cakrawala: Jurnal Pendidikan, 2019)
Application of Problem Based Learning (PBL) model on Drama Text Writing SkillsThe purpose of this research is to describe the application of problem based learning learning models in drama writing skills. The problem is that the eighth grade students of SMPN 4 Pandak are still having trouble finding ideas or ideas in writing drama texts. The location of the study was at SMP Negeri 4 Pandak. The study was conducted in class VIII Cpada Semester II of the 2018/2019 Academic Year. The research subjects were students of class VIII C, with 28 students consisting of 13 male students and 15 female students. The data collection technique was carried out through observations on the skills of writing text and the practice of playing drama. The results of the study showed that there was an improvement in the learning outcomes and skills of students in class VIII C Drama Text Writing material. Before using the PBL model students who achieved mastery learning outcomes were 15 students or 53.6%, while 13 students or 46.4% were not yet finished. After using the PBL learning model there was an increase in student learning outcomes ie all students (28 students) completed their learning outcomes or 100%. Thus there was an increase in completeness by 46.4%.